2017
DOI: 10.24237/djes.2017.10111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Evaluation of Traffic Accidents for Principle Urban Streets in Arbil City in Iraq

Abstract: Traffic accidents are considered one of the most important problems in modern societies. Arbil city in Iraq suffers from this problem; it is considered the second major cause of death.The main objectives of this study are to analyze and evaluate the causes of traffic accidents by using the statistical analysis technique, and self-observation study. In this study Traffic accident data, Geometric condition data ,and Traffic condition data, related to the Arbil streets network was collected, prepared and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Absence of standard support and lack of periodic vehicle maintenance are the main possible factors for car faults that prompt unexpected malfunctions [4,18]. Furthermore, it is revealed that weather and road mishaps account for 2.4% and 1.2% of RTAs, respectively, indicating that adequate engineering and proper roadway structure and control of roads by traffic police play a positive role in reducing the number of RTAs, although it has been reported that road status is a basic risk factor of accidents [18,19]. Additionally, minimal causative error is caused by environmental effects (1.2%) expressing that seasonal changes of Sulaymaniyah weather did not have a great impact on RTAs in general.…”
Section: Resultsmentioning
confidence: 99%
“…Absence of standard support and lack of periodic vehicle maintenance are the main possible factors for car faults that prompt unexpected malfunctions [4,18]. Furthermore, it is revealed that weather and road mishaps account for 2.4% and 1.2% of RTAs, respectively, indicating that adequate engineering and proper roadway structure and control of roads by traffic police play a positive role in reducing the number of RTAs, although it has been reported that road status is a basic risk factor of accidents [18,19]. Additionally, minimal causative error is caused by environmental effects (1.2%) expressing that seasonal changes of Sulaymaniyah weather did not have a great impact on RTAs in general.…”
Section: Resultsmentioning
confidence: 99%
“…After the normalization matrix was completed, the next process was to determine the weight of each element. The weighting of the element in the matrix N was performed using equation (4).…”
Section: ) Establish a Pairwise Comparison Matrixmentioning
confidence: 99%
“…Road factor contributes 3% of accidents and increases to 34% when combined with other factors such as human factor and vehicle factor [3]. Geometric design of roads that do not comply with the standard [4]- [7], damaged road surface conditions [8], [9], dangerous roadside [10]- [12], unavailable and/or damaged street lighting [13], [14], unavailability of markers and low visibility of markers [15], [16] inappropriate signs [17], and pedestrian facilities that do not adequately function [18], [19] are some of the factors that cause traffic accidents from road infrastructure aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Fatalities were high among children, adolescents and young adults. In Erbil, the capital of the Kurdish region, RTAs were the second major cause of death (7). These estimates are very high especially when under-reporting is common throughout in the region (8).…”
Section: H E a Lt H A N D S A F E T Y I S S U E S I N T H E Co M M U mentioning
confidence: 99%